Possible cost reduction by applying MRP in a transformer manufacturing company of Bangladesh - Hasan, S. Mainul; Karim, A.N. Mustafizul (2002)
Local manufacturing industries generally do not pay adequate attention towards applying the state-of-the-art operations management techniques in inventory control, scheduling, material requirements planning (MRP) etc. The main identifiable reasons are lack of exposure to the concurrent techniques and facilities, exorbitantly high price of commercially available software and inadequate indigenous support systems. Moreover, the lack of knowledge about the benefits of using MRP in various aspects hindered its wide spread diffusion. Most of the local firms assume that the procurement of raw materials either in huge quantity at a time or in small amount from period to period without adopting any mathematical approach would not have any remarkable effect on the total inventory cost. Practically the situation is different and it has been found that the procurement of material applying an established algorithm instead of current practice could significantly reduce the total incremental inventory costs. In this respect educational software was used. This paper highlights the salient features of MRP application in a local transformer manufacturing industry and makes a comparison of the total inventory costs determined by following the user-defined approach and the standard lot-sizing approaches.